Extremely short embryonic period of the intertidal pulmonate limpet Siphonaria sirius (Pilsbry, 1895). (3rd July 2021) - Wada, Yoko; Yusa, Yoichi
ABSTRACT: Siphonariidae is a panpulmonate family that occurs in intertidal rocky shores worldwide within temperate to tropical areas. Although the egg masses of Siphonaria sirius are commonly found in lower intertidal rocky shores in summer, there is a lack of information on their embryonic development. We examined the embryonic development and duration of S. sirius both in the laboratory and in the field. The study was conducted in Shirahama, Wakayama, Japan, during the summer of 2014 and 2015. The embryonic developmental process of S. sirius was similar to that of other planktotrophic siphonariids. However, S. sirius hatched within four days after oviposition at 27.35°C in the laboratory, which is the shortest in the Siphonariidae. In the field, hatching occurred notably faster at 1.6 days after oviposition, although the average temperature (27.42°C) was similar to that in the laboratory. The presence of egg predators, as well as other environmental factors, may be responsible for the short embryonic period of this species, especially in the field.